Adjoint sensitivity analysis of nonlinear distortion in RF circuits - Tannir, Dani (2009)
Recently, an efficient moments based method for computing the third order intercept point of RF circuits was proposed. The moments based approach did not however provide sensitivity information. In this paper we propose a new method based on moments of the adjoint network. This new approach provides both the third order intercept point as well as its sensitivity in a very computationally efficient manner. As is generally the case in adjoint based methods, the sensitivity is provided with respect to all circuit parameters simultaneously.